Eficiência de óleos brutos vegetais no controle de Aceria guerreronis e sua compatibilidade com Typhlodromus (Anthoseius) ornatus (Acari: Eriophydae, Phytoseiidae) - Freitas, Giselle Santos de (2016)
The coconut mite Aceria guerreronis (Acari: Eriophyidae) is a key pest of coconut worldwide. Predatory mites of the family Phytoseiidae are considered its main natural enemies, being Typhlodromus (Anthoseius) ornatus frequently reported in association with this pest mite. Crude vegetal oils have been used to control this pest however, there are few studies on the effect of these oils to the coconut mite and to predatory mites. The study aimed to evaluate the toxicity and repellency of crude coconut and palm oils to the coconut mite and the predatory mite T. ornatus as well as to assess the sublethal effect of crude coconut oil in functional and numerical response of the predatory mite T. ornatus. The predatory mite T. ornatus is 6.43 times mo re tolerant to crude coconut oil and 3.84 times more tolerant to crude palm oil than the coconut mite. The LC50 of crude palm oil, estimated for A. guerreronis, did not repel the predatory mite and repelled the coconut mite only after 1 hour of exposure. The LC99 of crude palm oil repelled the predator only after 1 hour of exposure and was repellent to the coconut mite after 1 and 24 hours. Only the LC99 of crude coconut oil was repellent to the coconut mite, but was not repellent to the predator. Additionally, sprayed and unsprayed females of T. ornatus presented a type III functional response, indicating that the mortality of prey increase with increasing density irrespective of oil spraying. Handling time and attack rate did not changed by exposing the predator to crude coconut oil. The oviposition of predator females exposed to distilled water increased until the density 200, from which there was a dramatic reduction in egg production, but for females exposed to crude coconut oil, there was an increasing number of eggs produced although with a lower peak. In conclusion, the crude coconut and palm oils were more toxic and repellent to coconut mite in comparison with the predatory mite T. ornatus, and the coconut oil is compatible with this predator. Therefore, both oils could be used in management programs of this pest mite